Cables interconnected with tuned inerter damper for vibration mitigation. (15th November 2017) - Sun, Limin; Hong, Dongxiao; Chen, Lin
Highlights: Inerter elements are integrated into hybrid cable networks for vibration control. A two-cable interconnected with a tuned inerter damper (TID) is studied in detail. An approximate method is presented for optimal tuning of the TID to a cable mode. The proposed system is found advantageous for multi-mode cable vibration control. Abstract: Cables in cable-stayed bridges are susceptible to vibrations induced by wind, wind/rain and indirectly by bridge tower and deck vibrations. It is common practice nowadays to supplement cable damping through external devices. However, for long stay cables, the damping provided by near-anchorage dampers is no longer sufficient. A hybrid cable network consisting of both dissipative devices and cross-ties is found to be a promising solution in this scenario. This study further proposes to embed inerter components into cable networks to improve their dissipation capacity. Specifically, a system of two cables interconnected with a Tuned Inerter Damper (TID) is studied. The system dynamics is formulated via complex modal analysis and system complex frequencies are characterized via parametric analysis. General tuning principle has been found when using the TID to maximize single mode damping and an approximate method is presented for efficient determining the TID parameters for optimal tuning and the corresponding damping ratio. Furthermore, the advantage of proposed system is shown by comparing with other passive strategies for multi-mode cable vibration control.